2020
DOI: 10.3390/atmos12010022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Heterogeneity of Tourists’ Choices under Climate Change Risks: A Segmentation Analysis

Abstract: This paper undertakes a data-driven segmentation analysis on tourists’ choice of island destinations in the context of a changing climate. To this end, 2528 tourists visiting ten European islands in the Mediterranean, Baltic, and Atlantic regions were posed hypothetical situations in which diverse impacts caused by CC (i.e., beach loss, heatwaves, storm intensification, etc.) were affecting the islands being visited. In each scenario, tourists’ responses ranged from stay on the island to change to an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Nonetheless, in this study, when jointly analyzing the three key questions, although a general moderate sensitivity is observed, we found that CC impacts may limit users' beach visits. This relates to another study in which 23% of tourists would not tolerate CC impacts on beaches, highlighting a special concern regarding the conditions in these environments above others, whereas about 30% of tourists are known to be willing to visit tourist destinations despite CC impacts [55]. Considering different CC impacts, however, very different perceptions are shown as discussed hereinafter; changes in temperature and beach area reduction appeared to be more limiting and decisive factors than water restrictions in future CC scenarios.…”
Section: Beach Users' Perceptions Of Impacts Of CC and Potential Adap...mentioning
confidence: 79%
“…Nonetheless, in this study, when jointly analyzing the three key questions, although a general moderate sensitivity is observed, we found that CC impacts may limit users' beach visits. This relates to another study in which 23% of tourists would not tolerate CC impacts on beaches, highlighting a special concern regarding the conditions in these environments above others, whereas about 30% of tourists are known to be willing to visit tourist destinations despite CC impacts [55]. Considering different CC impacts, however, very different perceptions are shown as discussed hereinafter; changes in temperature and beach area reduction appeared to be more limiting and decisive factors than water restrictions in future CC scenarios.…”
Section: Beach Users' Perceptions Of Impacts Of CC and Potential Adap...mentioning
confidence: 79%
“…In contrast, 50 units (72%) in the Southeast region had no climate change information on their webpages. Several studies point to differences among audience segmentation in regards to perceptions of climate change communication (Akerlof et al, 2011; De Urioste-Stone et al, 2016; Lam-González et al, 2021), which could be attributed to regional influences and beliefs surrounding the topic. The geography of a region itself may be a barrier to effective climate change interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that climate change has a direct impact on visitors’ travel behavior, and will continue to do so in the future (De Urioste-Stone et al, 2016; Fisichelli et al, 2015). Some sources report a visitor’s hypothetical decision to postpone or cancel their trips altogether under certain climate scenarios (Lam-González et al, 2021), while other studies point to an extension of visitor seasons with warming temperatures (Albano et al, 2013). Communicating the current and anticipated impacts of a changing climate will become increasingly vital as the phenomenon plays a stronger role in a park visitor’s trip planning considerations.…”
Section: Discussionmentioning
confidence: 99%
“…As climate change becomes more evident, the influence of extreme weather events on the tourism sector has become a growing field of academic research, both from the supply and demand side [10][11][12]. Thus, there is still a need to expand knowledge on tourists' resilience to climatic conditions in visited tourism destinations and their behavioral responses.…”
Section: Introductionmentioning
confidence: 99%